Arundinella tengchongensis (Poaceae), a name at new rank and newly combined based on morphological and molecular data. (1st October 2021) - Jiang, Li‐Qiong; Peng, Hua; Wang, Yue‐Hua
Abstract : To clarify the taxonomic status of Arundinella setosa var. tengchongensis and its relationships with A. setosa var. setosa and other related species, molecular phylogenetic analyses based on nuclear ITS and two plastid DNA ( matK and trnL‐F ) sequences, and morphological comparisons using one‐way ANOVA were carried out. Our results reveal that A. setosa var. tengchongensis phylogenetically belong in a different clade separated from the type variety. Morphologically, A. setosa var. tengchongensis is easily distinguished from A. setosa var. setosa and other varieties by its smaller spikelets, shorter awns and bearded nodes. Thus, A. setosa var. tengchongensis is here elevated to species rank and newly combined as A. tengchongensis .